PENYUSUNAN ALFABET MEMBENTUK KATA MENGGUNAKAN ALGORITMA GENETIKA - Saragih, Rijois Iboy Erwin (UNIVERSITAS PELITA HARAPAN, 2017)
Genetic algorithm is heuristic searching algorithm which based on nature selection of mechanism and nature genetic. The basic concept that inspires the genetic algorithm is that evolution theory. The word is consisted of the alphabet. Alphabet is a set of letters or other characters with which one or more languages are written especially if arranged in a customary order. In this research will use genetic algorithm to form a word based on the typing word. The final result of this research is that showing the exact word that is typed.